METHODOLOGY FOR EVALUATING THE EFFECTIVENESS OF INVESTMENTS IN THE EXPANSION OF UNIVERSITY HOUSING INFRASTRUCTURE - Chikibayeva Zarina Nikolayevna; Shalbolova Urpash Zhaniyazovna (Scientific Journal of Pedagogy and Economics, 2021)
The article deals with the problem of assessing the socio-economic efficiency of investment in the expansion of University housing infrastructure. Evaluating the effectiveness of investment design solutions is the main approach to determining the return on investment of financial resources in expanding the Fund of student dormitories, in which both investors and all participants in the implementation of investment projects for the construction and modernization of student dormitories are interested. To determine the socio-economic efficiency of the investment project for the construction of housing infrastructure of higher education institutions, a system of indicators was formed. Methods for calculating the socio-economic efficiency of housing infrastructure investment projects based on qualitative and quantitative criteria are considered. A step-by-step implementation of methods for assessing the socio-economic efficiency of projects for the modernization of student housing stock is presented. Since all regions of Kazakhstan set the task of expanding the University's housing infrastructure through the construction of new and reconstruction of existing dormitories with the use of public-private partnerships, there is a need to expand student housing Fund, which is based on the data of the operator of the state program of JSC "Financial center" of the MES RK, which determines the need, funding sources, manage cash flow to ensure the introduction of new places in hostels for students, undergraduates and doctoral students, draws up contracts with investors.